Organization Learning, Dissemination of Knowledge and Organizational Performance in Nepalese Banking Sectors - Parajuli, Suman Kamal; Mahat, Dipak; Lingden, Binod (Nepal Journal of Multidisciplinary Research, 2022)
In today's increasingly competitive business climate, the adoption of a learning organization and knowledge transfer strategy has emerged as an essential component for the continued viability of any organization. Seated on this theme, the study objective is to understand the employee’s views on organizational learning, dissemination of knowledge, and organizational performance in the Nepalese public and private sectors. The study consists of 200 employees, five public sectors and five private sectors of Nepal. The structured survey questionnaire was used for the data collection, Mean and standard deviation was used to measure the perception of respondents. Cronbach's alpha was employed to measure the reliability. Findings shows that organizational performance seem better in private and public sectors of Nepal but the organization learning activities and knowledge dissemination seem low.so there is need to develop the learning culture and transfer of knowledge in order meet the competitive business climate. Further researcher can discover the model of organization learning, knowledge management and organization performance adopted by Nepalese organization.